2023
DOI: 10.14710/jrkm.2023.18844
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengetahuan terhadap Kepatuhan Konsumsi Tablet Tambah Darah dengan Kejadian Anemia pada Remaja Putri

Ana Soraya Siyami,
Khamidah Achyar,
Inggar Ratna Kusuma

Abstract: Anemia is one of the problems of various public health problems that globally affect 1.62 billion people in the world. Anemia in young women is still a big public health problem because the prevalence is still around 20%, which is 21.7%. Anemia status in adolescents is thought to be influenced by several factors, namely knowledge and adherence to taking iron tablets. The purpose of this study was to describe and analyze the relationship between knowledge and adherence to blood supplement consumption with the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…The recommendations given are often not followed correctly, as evidenced by research conducted by Siyami et al (2023), which found a low proportion of adolescents who consume TTD regularly during menstruation. This can happen for several reasons, such as forgetfulness, boredom, laziness, not feeling the need, the metallic taste of iron supplements, and the presence of side effects such as dizziness, nausea, and drowsiness after taking TTD (Hamranani et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The recommendations given are often not followed correctly, as evidenced by research conducted by Siyami et al (2023), which found a low proportion of adolescents who consume TTD regularly during menstruation. This can happen for several reasons, such as forgetfulness, boredom, laziness, not feeling the need, the metallic taste of iron supplements, and the presence of side effects such as dizziness, nausea, and drowsiness after taking TTD (Hamranani et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Tingginya angka kejadian anemia pada remaja putri berkaitan erat dengan adanya penurunan kadar hemoglobin dalam tubuh. Status gizi merupakan salah satu faktor yang mempengaruhi kejadian anemia pada remaja putri (Sibagariang, 2014). Faktor lain yang berpengaruh, yaitu siklus menstruasi, pola makan, serta kualitas tidur yang kurang baik (Musrah & Widyawati, 2019).…”
unclassified